ضوابط استعمال الحوافز التجارية في التسويق: الطومبولا انموذجا - هشام, غربي (University of Eloued جامعة الوادي, 2019)
"تناول هذا البحث في طياته "" ضوابط استعمال الحوافز التجارية في التسويق "" والتي تعتبر من الوسائل الحديثة المستعملة في تنشيط المبيعات، وهي نتاج التطور الكبير الحاصل في المعاملات التجارية. تمت دراسة هذا الموضوع من خلال خمسة مباحث، حيث خصص المبحث الأول للتعريف ﺑﺎلتسويق والحوافز التجارية وذكر أهميتها، أما المباحث الثلاثة التي تليه، فقد خصصنا كل مبحث للكلام على نوع من أنواع الحوافز التجارية مع ذكر صورها الغالب استعمالها في التسويق، لنتطرق بعد ذلك للتكييف الفقهي والحكم الشرعي، ثم ننهي كل مبحث بذكر الضوابط التي يجب التقيد ﺑﻬا لاستعمال ذلك النوع من الحوافز التجارية في التسويق، أما المبحث الخامس فقد خصص لدراسة الطمبولا كنموذج للحوافز التجارية، وكانت دراسة تطبيقية من خلال مهاتفة احدى شركات البُن التي تستعمل هذا النوع من الحوافز، وطرحنا عليها مجموعة من الأسئلة حتى تتضح لنا الصورة التي سنبني عليها الحكم الشرعي، لنختم المبحث ﺑﺎلنتائج التي وصلنا اليها من خلال هذه الدراسة التطبيقية، وختمت هذه الدراسة بخاتمة احتوت على اهم النتائج المتوصل اليها مع تقديم اهم التوصيات." "The study deals with ‘(Islamic) standards for using commercial incentives in marketing - Tombola case of study’. Commercial incentives is considered as one of the modern means used to stimulate sales, which is the result of the great development in commercial transactions. This topic was studied through five chapters. The first one was about the definition of marketing, commercial incentives as a concept and their types. The next three chapters, each one deals with one type of commercial incentives types by mentioning the possible forms that usually used in marketing. Then we moved to speak about framing this form in jurisprudence and giving it the right judgment according to Islamic law. At the end of each chapter, we list the Islamic standards for using each form of commercial incentives. For the fifth chapter, it deals with Tombola as a case of study. By calling one of the coffee companies that use this kind of incentives and we asked set of questions to clarify how they use the incentive in order to give the right Islamic judgment. The study is ended with the main reached findings and with the most important recommendations."
مذكرة ماستر تخصص معاملات مالية معاصرة
Keywords: الحوافز التجارية، التسويق، تنشيط المبيعات، الطمبولا; "commercial incentives, marketing, stimulate sales, Tombola"